Experiments on energy, the environment, and sustainability - Isaac, R. Mark (Robert Mark), 1954-; Norton, Douglas A., 1984- (Bingley, U.K. : Emerald, 2011)
This volume will present experimental economics research focusing on issues of environmental quality and sustainability. Specific topics will include institutions for cap-and-trade, eco-tourism, urban sprawl, and optimal pollution control strategies. In addition to the traditional'introduction', we are asking an expert on engineering issues in energy, the environment, and sustainability to write an essay highlighting the benefits to scientists and engineers of understanding human behaviour.
Introduction / R. Mark Isaac, Douglas A. Norton -- Price discovery in emissions permit auctions / Dallas Burtraw, Jacob Goeree, Charles Holt, Erica Myers, Karen Palmer, William Shobe -- An experimental analysis of grandfathering versus dynamic auctioning in the EU ETS / Anabela Botelho, Eduarda Fernandes, Lia Costa Pinto -- Framing effects in an emissions trading experiment with voluntary compliance / Timothy N. Cason, Leigh Raymond -- Behavior in a dynamic environment with costs of climate change and heterogeneous technologies : an experiment / Svetlana Pevnitskaya, Dmitry Ryvkin -- Contracts, behavior, and the land-assembly problem : an experimental study / Kurtis Swope, Ryan Wielgus, Pamela Schmitt, John Cadigan -- An experimental study for environmental fundraising in Majorca, Spain / Maria Claudia Lopez, Esther Blanco, Eric A. Coleman -- Energy systems, economics, and sustainability / David Cartes.
Keywords: Environmental economics